Endoscopic-Assisted Flexor Hallucis Longus Transfer: Harvest of the Tendon at Zone 2 or Zone 3 - Lui, Tun Hing (Arthrosc Tech, 2015)
Flexor hallucis longus (FHL) tendon transfer is indicated for reconstruction of the Achilles tendon with a gap larger than 5 cm. The tendon can be harvested at zone 2 or zone 3 by minimally invasive techniques with the advantage of minimal soft-tissue dissection. The tendon can be harvested under the sustentaculum tali by zone 2 FHL tendoscopy. It is adequate for FHL transfer to the posterior calcaneal tubercle. If a double-thickness reconstruction of a huge gap of the Achilles tendon is indicated, the tendon can be harvested at the level of the hallux by means of a tendon stripper. However, the interconnection tendon of the master knot of Henry can be split together with the FHL or flexor digitorum longus tendon instead of being cut. Zone 2 FHL tendoscopy can be used to release the split tendon to complete the FHL harvest.